2017
DOI: 10.2147/dmso.s129247
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Mexico: prevalence, comorbidities, associations with patient outcomes, and treatment experiences

Abstract: ObjectiveThe goal of this study is to investigate obesity and its concomitant effects including the prevalence of comorbidities, its association with patient-reported outcomes and costs, and weight loss strategies in a sample of Mexican adults.MethodsMexican adults (N=2,511) were recruited from a combination of Internet panels and street intercepts using a random-stratified sampling framework, with strata defined by age and sex, so that they represent the population. Participants responded to a survey consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 48 publications
4
46
0
6
Order By: Relevance
“…The prevalence of overweight and obesity in Mexico is among the highest in the world [27]. In 2016, the National Survey of Health and Nutrition (ENSANUT) determined that an estimated 72.5% of Mexican adults are overweight or obese [28], and that growth in the prevalence of obesity had plateaued in urban areas but continues to rise in rural areas [28].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of overweight and obesity in Mexico is among the highest in the world [27]. In 2016, the National Survey of Health and Nutrition (ENSANUT) determined that an estimated 72.5% of Mexican adults are overweight or obese [28], and that growth in the prevalence of obesity had plateaued in urban areas but continues to rise in rural areas [28].…”
Section: Introductionmentioning
confidence: 99%
“…25 In Mexico, the prevalence of obese or overweight people reported in 2017 was 62%. 3 Some authors showed that prevalence is expected to increase to 88% for men and 91% for women for 2050. 26 In the present study, we found 75% prevalence of overweight and obesity in women and 76% in men.…”
Section: Discussionmentioning
confidence: 99%
“…2 It was previously reported that 62% of Mexican adults are at least overweight. 3 Adipose tissue is considered an important endocrine organ with high lipid storage capacity for systemic management of energy substrates. Excessive lipid loading produces adipocyte stress with the ability to cause adverse effects on obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Mexico is among the most negatively affected countries by obesity-related comorbidities. Given the accelerated increase of chronic diseases worldwide, it is essential to take action to address this health problem [39]. In this focused study, the nutritional practices of a speci c Mexican population were examined with an intent to elucidate a possible adiponectin association with nutritional and sociodemographic characteristics in young students from the Los Altos, Jalisco region of Mexico.…”
Section: Discussionmentioning
confidence: 99%